2019
DOI: 10.15171/ps.2019.51
|View full text |Cite
|
Sign up to set email alerts
|

Comments on "What if Cocrystallization Fails for Neutral Molecules? Screening Offered Eutectics as Alternate Pharmaceutical Materials: Leflunomide-A Case Study"

Abstract: -

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Drugs with outliers tend to have higher molecular weight and more acidic functional groups, which are not clearly expressed in the training set. In addition, it may also be influenced by the quality of the collected data, such as the validity of applied melting point and melting enthalpy data . Accordingly, these results also indicate the requirement of further expanding the dataset to adequately obtain the features of multiple drugs so that the solubility of the drug in various solvents can be more accurately predicted.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Drugs with outliers tend to have higher molecular weight and more acidic functional groups, which are not clearly expressed in the training set. In addition, it may also be influenced by the quality of the collected data, such as the validity of applied melting point and melting enthalpy data . Accordingly, these results also indicate the requirement of further expanding the dataset to adequately obtain the features of multiple drugs so that the solubility of the drug in various solvents can be more accurately predicted.…”
Section: Resultsmentioning
confidence: 99%
“…Acree Jr et al compared the reported melting point and melting enthalpy data of multiple drugs and found that data may be influenced by a number of factors, such as the experimental device, the method of experiment, and the purity of the experimental sample. 33 Therefore, in this work, according to the current problems of available models, we focused on developing an explainable strategy that combines molecular thermodynamics and machine learning to predict the solubility of drugs in various solvents. PC-SAFT was utilized to model drugs and solvents as a representative theory of molecular thermodynamics.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation